Developing Genially-Based Interactive Learning Media to Enhance Motivation and Learning Outcomes of Grade XI Students on Reaction Rate Concepts - Ainun Mudmainnaa; Muh. Muharram; Moh. Wijaya (Jurnal Penelitian Pendidikan IPA, 2026)
Chemistry in Indonesia continues to face persistent challenges related to student motivation and academic performance, particularly on abstract topics such as reaction rates. This study aimed to develop, validate, and evaluate a Genially-based interactive learning medium integrated within the Discovery Learning model for Grade XI students at SMAN 9 Pinrang. A Research and Development (R&D) approach was employed using the ADDIE model, encompassing five systematic phases: Analysis, Design, Development, Implementation, and Evaluation. The research subjects comprised 31 students of class XI.2. Data were gathered through structured interviews, questionnaires, expert validation sheets, and written learning outcome tests. The results demonstrated that: (1) the Genially interactive media was successfully developed across all five ADDIE phases, from needs and curriculum analysis through prototype design, expert validation, field implementation, and final evaluation; (2) the media achieved a validity rating of 3.70 out of 4.00 (92%), classified as highly feasible; (3) practicality was confirmed by teacher response scores of 97.08% and student response scores of 89%, both categorized as highly practical; and (4) effectiveness was evidenced by a substantial increase in student motivation from 61.70% to 96.19%, a class completion rate of 90%, and a mean post-test score of 90.65, surpassing the minimum mastery criterion of 80. These findings confirm that Genially-based interactive media represents a valid, practical, and effective instructional tool capable of meaningfully improving both motivational engagement and cognitive outcomes in secondary chemistry education.